Determinan Perilaku Keuangan Gen Z: Antara Literasi Keuangan, Financial Technology dan Gaya Hidup Hedonis - Irma Christiana; Nanda Saputra; Linzzy Pratami Putri (Universitas Muhammadiyah Palembang, 2025)
Purpose– The aim of this research is to ascertain and examine how financial technology, hedonistic lifestyle, and financial literacy affect financial behavior. Design/methodology– An explanatory research method was used in this study. The data used were obtained from questionnaires and documentation. The population in this study was Gen Z, born between 1997 and 2012, living in the Binjai Barat subdistrict of Binjai City. The sample was selected randomly (accidental sampling). The sample size was determined using the Lemeshow formula, resulting in 96 respondents as the sample. To facilitate the research, the sample size was rounded up to 100 respondents. The data was analyzed using multiple linear regression with the help of IBM SPSS Statistics. Findings - The results of the study indicate that the variables of financial literacy, fintech, and hedonistic lifestyle together have a positive and significant effect on the financial behavior of Gen Z in the Binjai Barat District of Binjai City. Partial hypothesis testing shows that fintech and hedonistic lifestyle do not affect financial behavior. Conversely, financial literacy affects the financial behavior of Gen Z.